VALIDATION OF OVSYNCH AND HEAT SYNCH PROTOCOL IN POST PARTUM ANOESTRUS COWS - MAHTO, DINESH (The Indian Journal of Animal Reproduction, 2023)
Thirty anoestrus postpartum crossbred cows were randomly selected and equally divided into three groups.Group I and II animals were treated with ovsynch and heat synch protocol along with supplementation of Mineral bolus,Phosphorus inj and Dewormer (Fenbendazole), respectively and groups III control groups administered with Mineralbolus, Phosphorus inj and Dewormer (Fenbendazole). The cows in Group I and II showed the conception rate of 60 %and 50 % at induced estrus as against 20 % in control groups. It is concluded that Ovsynch protocol along with mineralmixture supplement has improved the conception rate in postpartum cows.
Keywords: Ovsynch; heat synch; Anestrous; Postpartum and cow